2008
DOI: 10.1159/000162297
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Bone Metabolism

Abstract: Background: There are data to suggest low bone mineral density is disproportionately prevalent among those with psychiatric disorders. This paper aims to review the current evidence on the relationship between depression and bone mineral density, and identify potential mechanisms. Methods: Relevant sources were identified from the Pubmed and Web of Science (ISI) databases from the first relevant publication in 1994 to the present, 2007, using a combination of key words and terms including depression, major dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 297 publications
1
28
0
Order By: Relevance
“…First, as depression itself has been shown to be a risk factor of osteoporosis [1922], incomplete elimination of the impact of disease severity (or other potential confounders) during the matching process could affect our findings, especially in our cohort with depression diagnoses. Another limitation comes from our assessment of medication exposure.…”
Section: Discussionmentioning
confidence: 99%
“…First, as depression itself has been shown to be a risk factor of osteoporosis [1922], incomplete elimination of the impact of disease severity (or other potential confounders) during the matching process could affect our findings, especially in our cohort with depression diagnoses. Another limitation comes from our assessment of medication exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Increased hypothalamic-pituitary-adrenal (HPA) axis activity and stress hormone levels are known to affect metabolism, causing alterations in visceral adiposity and insulin sensitivity. Chronic stress also affects bone turnover, leading to "lowturnover" osteoporosis (12,13,56,61). Involuntary forms of exercise such as swimming and forced treadmill running increase serum biomarkers of stress in rats (15), and even voluntary wheel running has been shown to increase corticosterone secretion (7, 21).…”
mentioning
confidence: 99%
“…Also consistent with this hypothesis, many studies have found associations of depression with high bone turnover [5860]. Individuals with major depression have increased levels of proinflammatory cytokines [6163] and circulating cortisol [6466], as do socially disadvantaged individuals [6775].…”
Section: Discussionmentioning
confidence: 80%